Accelerated flooding along the U.S. East Coast: On the impact of sea‐level rise, tides, storms, the Gulf Stream, and the North Atlantic Oscillations. (11th August 2014) - Ezer, Tal; Atkinson, Larry P.
Abstract Recent studies identified the U.S. East Coast north of Cape Hatteras as a "hotspot" for accelerated sea‐level rise (SLR), and the analysis presented here shows that the area is also a "hotspot for accelerated flooding." The duration of minor tidal flooding [defined as 0.3 m above MHHW (mean higher high water)] has accelerated in recent years for most coastal locations from the Gulf of Maine to Florida. The average increase in annual minor flooding duration was ∼20 h from the period before 1970 to 1971–1990, and ∼50 h from 1971–1990 to 1991–2013; spatial variations in acceleration of flooding resemble the spatial variations of acceleration in sea level. The increase in minor flooding can be predicted from SLR and tidal range, but the frequency of extreme storm surge flooding events (0.9 m above MHHW) is less predictable, and affected by the North Atlantic Oscillations (NAO). The number of extreme storm surge events since 1960 oscillates with a period of ∼15 year and interannual variations in the number of storms are anticorrelated with the NAO index. With higher seas, there are also more flooding events that are unrelated to storm surges. For example, it is demonstrated that week‐long flooding events in Norfolk, VA, are often related to periods of decrease in the Florida Current transport. The results indicate that previously reported connections between decadal variations in the Gulf Stream (GS) and coastal sea level may also apply to short‐term variations, so flood predictions may be improved if the GS influence is considered.